2020
DOI: 10.1038/s41467-020-16220-w
|View full text |Cite
|
Sign up to set email alerts
|

Dietary serine-microbiota interaction enhances chemotherapeutic toxicity without altering drug conversion

Abstract: The gut microbiota metabolizes drugs and alters their efficacy and toxicity. Diet alters drugs, the metabolism of the microbiota, and the host. However, whether diet-triggered metabolic changes in the microbiota can alter drug responses in the host has been largely unexplored. Here we show that dietary thymidine and serine enhance 5-fluoro 2′deoxyuridine (FUdR) toxicity in C. elegans through different microbial mechanisms. Thymidine promotes microbial conversion of the prodrug FUdR into toxic 5-fluorouridine-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 65 publications
(92 reference statements)
0
35
0
1
Order By: Relevance
“…It is worth mentioning application of nanotechnology targeting gut microbiota. However, it should still be warned that some drugs with therapeutic effects may become toxic after being metabolized by gut microbiota ( Ke et al, 2020 ; Javdan et al, 2020 ). Therefore, patients with gastrointestinal lesions should be requested to be treated with drugs that could both protect gastrointestinal functions.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning application of nanotechnology targeting gut microbiota. However, it should still be warned that some drugs with therapeutic effects may become toxic after being metabolized by gut microbiota ( Ke et al, 2020 ; Javdan et al, 2020 ). Therefore, patients with gastrointestinal lesions should be requested to be treated with drugs that could both protect gastrointestinal functions.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, cancer-associated microbiota’s ability to modulate antitumor immune activation and therapy response might involve the direct provision to tumor cells of nutrients derived from microbial sources not only at the primary tumor sites but also at metastatic localizations [ 194 , 195 , 196 , 197 ]. This scenario adds even more complexity to the systemic (e.g., insulin-lowering effects of the ketogenic diet) versus cell-autonomous effects (e.g., restriction of serine/glycine or methionine) of dietary interventions [ 198 ], especially when considering recent evidence showing that diet-microbe interactions can alter the host response to drugs without altering the drug or the host [ 199 ]. Nonetheless, the extent of inter-patient variability in normal metabolism further highlights the need for controlled studies with metabolic therapies and/or dietary interventions in varied populations before new developments in combination with ICIs could be carried out.…”
Section: Gaps and Limitations Of Immunotherapy-boosting Metabolicmentioning
confidence: 99%
“…Another aspect of modulating gut microbiota is the change in metabolism by diet or probiotics [109,117,118]; this may not only modulate metabolism of normal metabolites, but also signaling, miRNA expression, and cross-talk between microbiota and mammalian cells (normal and tumor), subsequently altering the host response to the drug. It has also been demonstrated that crosstalk may be mediated by extracellular vesicles, which can carry not only proteins but also RNA and DNA, which may modulate genetic expression [119]…”
Section: Expert Opinionmentioning
confidence: 99%